2019
DOI: 10.1002/acn3.731
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, double‐blind, placebo‐controlled study of interferon‐γ 1b in Friedreich Ataxia

Abstract: Objective In vitro, in vivo, and open‐label studies suggest that interferon gamma (IFN‐γ 1b) may improve clinical features in Friedreich Ataxia through an increase in frataxin levels. The present study evaluates the efficacy and safety of IFN‐γ 1b in the treatment of Friedreich Ataxia through a double‐blind, multicenter, placebo‐controlled trial. Methods Ninety‐two subjects with FRDA between 10 and 25 years of age were enrolled. Subjects received either IFN‐γ 1b or placebo for 6 months. The primary outcome mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…Other approaches tried to enhance frataxin transcription or translation. Interferon-γ (22), erythropoietin (23), or epigenetic modifiers such as histone deacetylase inhibitors (HDACis) (4,24) showed promising frataxin induction in in vitro and in vivo models, but the former 2 failed to reach endpoints in clinical trials (25,26) and the latter requires pharmacologic optimization to improve efficacy and reduce toxicity (27).…”
Section: Introductionmentioning
confidence: 99%
“…Other approaches tried to enhance frataxin transcription or translation. Interferon-γ (22), erythropoietin (23), or epigenetic modifiers such as histone deacetylase inhibitors (HDACis) (4,24) showed promising frataxin induction in in vitro and in vivo models, but the former 2 failed to reach endpoints in clinical trials (25,26) and the latter requires pharmacologic optimization to improve efficacy and reduce toxicity (27).…”
Section: Introductionmentioning
confidence: 99%
“…16 This resulted in the new, modified FARS (mFARS) score (mFARS, 93), which is used in currently ongoing and recently finished clinical trials. [30][31][32][33] It is important that all items of the mFARS are included in the full FARSn examination; only the bulbar subscore (mA) was modified (now excluding items A1, facial atrophy and A2, and tongue atrophy), and the peripheral nervous system (D) subscore is now omitted. The remaining subscales, upper limb coordination (B), lower limb coordination (C), and upright stability (E), are identical in both the mFARS and the FARSn (see figure 1 for description and scoring for overall scales and individual subscales).…”
Section: Friedreich Ataxia Rating Scalementioning
confidence: 99%
“…Moreover, the wrong timing in drug dosing caused transient side effects to interfere with the neurological assessments. Nevertheless, in the open‐label extension of the study, the patients who received IFNγ for 52 weeks showed a more stable disease course compared to the natural history data …”
mentioning
confidence: 94%